A review of network traffic analysis targeting mobile devices - Ming XU; Xue YANG; Jianwu ZHANG (Dianxin kexue)
Mobile devices are now ubiquitous in people’s life,thus analyzing network traffic generated by these devices can provide valuable information for network management and privacy preservation.In order to review the works that contribute to the state of the art of network analysis targeting mobile devices,the framework of network analysis,traffic collection approaches were introduced and a classification of the works according to the goal of the analysis was presented.Finally,the future research of network analysis targeting mobile devices was proposed based on the current problems in this literature.